Safety of In-Hospital Only Thromboprophylaxis after Fast-Track Total Hip and Knee Arthroplasty: A Prospective Follow-Up Study in 17,582 Procedures - Petersen, Pelle Baggesgaard; Kehlet, Henrik; Jørgensen, Christoffer Calov; on behalf of the Lundbeck Foundation Centre for Fast-track Hip and Knee Replacement Collaborative Group (Thrombosis and Haemostasis, 2018)
Most international guidelines recommend pharmacological thromboprophylaxis after total hip and knee arthroplasty (THA/TKA) for 10 to 35 days. However, a recent cohort study on fast-track THA and TKA questioned the need for prolonged thromboprophylaxis when length of stay (LOS) is ≤ 5 days. We aimed at re-investigating the incidence of venous thromboembolism (VTE) in fast-track THA and TKA with in-hospital only thromboprophylaxis when LOS was ≤ 5 days. Prospective cohort study from 1 December 2011 to 30 October 2015 on elective unilateral THA/TKA with in-hospital only thromboprophylaxis if LOS was ≤ 5 days. Prospective information on co-morbidity and complete 90-day follow-up through the Danish National Patient Registry and medical records. Patients with pre-operative use of anticoagulants were excluded. In per protocol analysis, 17,582 (95.5%) had LOS of ≤ 5 days (median, 2 [interquartile range, 2–3]) and in-hospital thromboprophylaxis only. Incidence of symptomatic VTE was 0.40%, consisting of 28 (0.16%) pulmonary embolisms (PEs), 38 (0.22%) deep vein thrombosis (DVT) and 4 (0.02%) combined DVT and PE. Two PEs (0.01%) were fatal. VTE-associated risk factors with in-hospital only thromboprophylaxis were age > 85 years, odds ratio (OR) of 3.74 (95% confidence interval: 1.15–12.14, p = 0.028), body mass index (BMI) of 35 to 40, OR of 2.55 (1.02–6.35, p = 0.045) and BMI > 40, OR of 3.28 (1.02–10.56, p = 0.046). In conclusion, 90-day incidence of VTE after fast-track THA and TKA with in-hospital thromboprophylaxis only was 0.40%. Prolonged thromboprophylaxis may be reserved for LOS > 5 days or specific high-risk patients, but requires further studies regarding optimal type and duration of thromboprophylaxis.
Keywords: fast-track; enhanced recovery; arthroplasty; thromboprophylaxis; venous thromboembolism